MODERN DIAGNOSTIC METHODS AND INDICATORS FOR EVALUATING THE EFFECTIVENESS OF VIRTUAL LABORATORIES - Buranova Jazira Ergash kizi (Modern American Journals, 2025)
This article explores contemporary diagnostic approaches and assessment indicators used to evaluate the effectiveness of virtual laboratories in educational environments. The paper examines technological, pedagogical, and psychological criteria for diagnostics, along with performance metrics that reflect student engagement, learning outcomes, and system usability. The study emphasizes the growing role of virtual laboratories in STEM education and highlights methods that ensure their quality, reliability, and long-term educational value.
Keywords: Virtual laboratories, digital diagnostics, educational technology, learning analytics, assessment indicators, STEM education